2013
DOI: 10.2176/nmc.53.537
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic Management of Pregnant Women With Stroke

Abstract: Stroke during pregnancy is rare, but after occurring, most patients develop serious neurological conditions. Hemorrhagic stroke, including intracerebral hemorrhage and subarachnoid hemorrhage, often requires emergency surgical intervention. In addition to significant maternal physiological changes, the potential for fetal harm should be considered during anesthetic management of these patients. Whether cesarean section or neurosurgical intervention should be prioritized or performed simultaneously in pregnant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
5
0
2
Order By: Relevance
“…management of hypotension, use of osmotic diuretics, and mechanical hyperventilation) may pose a risk to the fetus. 53
7.0 Poststroke antenatal obstetric considerations for women with a stroke in pregnancy i. Where possible, obstetric care should be managed with access to, or in collaboration with, stroke care.
…”
Section: Poststroke Antenatal Obstetric Considerations For Women Withmentioning
confidence: 99%
“…management of hypotension, use of osmotic diuretics, and mechanical hyperventilation) may pose a risk to the fetus. 53
7.0 Poststroke antenatal obstetric considerations for women with a stroke in pregnancy i. Where possible, obstetric care should be managed with access to, or in collaboration with, stroke care.
…”
Section: Poststroke Antenatal Obstetric Considerations For Women Withmentioning
confidence: 99%
“…Medical management of ICH typically does not require delivery in preterm fetuses. 16 It has been suggested that focus should be placed on maternal health for <26 to 28 weeks gestation, 32 with delivery via cesarean delivery for > 34 weeks gestation. 34 In general, cesarean delivery should be reserved for obstetric indications.…”
Section: Antepartum and Intrapartum Considerationsmentioning
confidence: 99%
“…A concurrent cesarean delivery may be considered if the fetus is viable. It has been suggested that if the gestational age is >28 to 32 weeks, cesarean delivery before craniotomy may improve fetal outcomes, given the fetal risk of neurosurgery 32. Fetal status should be optimized as much as possible before and during surgery, which may include continuous maternal cardiac monitoring, replacement of blood and clotting factors, avoiding drugs that may induce uterine relaxation or fetal depression, and positioning in the left lateral supine position if allowed by the neurosurgeon 1…”
Section: Introductionmentioning
confidence: 99%
“…Pregnant stroke patients, such as nonpregnant patients, have better outcomes when cared for at a specialized stroke center, and therefore, stabilization and emergent transfer may be indicated 62 . During the acute intervention, continuous electronic fetal monitoring may be performed to assess fetal well-being 84 . Consideration for maternal stability, gestational age, and the willingness to deliver if nonreassuring fetal status is identified should be addressed in a multidisciplinary fashion 85,86 .…”
Section: Managementmentioning
confidence: 99%
“…62 During the acute intervention, continuous electronic fetal monitoring may be performed to assess fetal well-being. 84 Consideration for maternal stability, gestational age, and the willingness to deliver if nonreassuring fetal status is identified should be addressed in a multidisciplinary fashion. 85,86 After intervention, the pregnancy can be allowed to progress to term if the maternal condition is favorable and stable.…”
Section: Obstetrical Care and Deliverymentioning
confidence: 99%